A pH-responsive pei / pan composite nanofiber membrane and a preparation method and application thereof
Patent Information
- Application Number
- CN202611156410.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-11-03
AI Technical Summary
Existing DNA storage systems suffer from insufficient storage stability, easy DNA degradation, and lack of intelligent response regulation. Traditional methods rely on ultra-low temperature cryopreservation, which is cumbersome, while emerging materials are prone to damaging the integrity of DNA structure during elution.
PEI/PAN composite nanofiber membranes were prepared using electrospinning technology. By utilizing the electrostatic interaction between the amino groups of PEI and DNA, the adsorption and release of DNA were achieved by adjusting the pH value, and a three-dimensional porous network structure was constructed to improve the contact area and flexibility.
It achieves efficient adsorption and controlled release of DNA, improves storage capacity and flexibility, simplifies the operation process, and ensures the structural integrity of DNA.
Smart Images

Figure CN123027699A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomaterials and DNA storage technology, specifically relating to a pH-responsive PEI / PAN composite nanofiber membrane, its preparation method, and its application in DNA storage. Background Technology
[0002] DNA, as a crucial carrier of genetic information, plays a central role in molecular biology research, gene therapy, and vaccine development. In many practical applications, it is often necessary to transfer DNA molecules from a liquid environment to a solid-phase support for loading and preservation, and then release them back into the liquid phase under specific conditions for subsequent use.
[0003] However, DNA is susceptible to various external factors such as temperature, humidity, and nucleases during storage, leading to DNA breakage and base damage. Traditional DNA storage often relies on ultra-low temperature cryopreservation, which is highly dependent on cold chain transportation equipment and inevitably involves repeated freeze-thaw cycles, further accelerating DNA degradation. On the other hand, existing nucleic acid storage materials are mostly designed for short-term extraction and purification, generally suffering from limited storage capacity and harsh elution conditions, easily damaging the structural integrity of the target DNA during the release phase. Furthermore, while emerging solid-phase storage materials such as silica or magnetic nanoparticles possess large specific surface areas, their microscopic powder state necessitates high-speed centrifugation for elution and recovery, resulting in cumbersome solid-liquid separation processes.
[0004] Polyacrylonitrile (PAN) possesses excellent mechanical properties, chemical stability, and fiber-forming properties, making it a commonly used electrospinning backbone material. However, its inherent brittleness and insufficient mechanical flexibility make it unsuitable as an ideal long-term DNA storage material on its own. Polyethyleneimine (PEI), a classic cationic polymer, contains numerous amino groups in its molecular chain, enabling it to efficiently adsorb negatively charged DNA molecules through electrostatic interactions and exhibiting good pH-responsive characteristics. However, to date, no research has been reported on developing a novel smart responsive material that combines PAN as a fiber backbone to provide structural support with the introduction of PEI as a functional component, achieving stable DNA preservation and controlled release. Summary of the Invention
[0005] Therefore, the purpose of this invention is to provide a pH-responsive PEI / PAN composite nanofiber membrane, its preparation method, and its application in DNA storage, so as to solve the problems of insufficient storage stability, easy DNA degradation, and lack of intelligent response regulation in existing DNA storage systems.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a pH-responsive PEI / PAN composite nanofiber membrane, wherein branched polyethyleneimine (PEI) and polyacrylonitrile (PAN) are dissolved in an organic solvent to form a mixed spinning solution, and a three-dimensional porous network structure composite nanofiber membrane is prepared by electrospinning.
[0007] Based on the above technical solution, the preparation method further includes the following steps: dissolving branched polyethyleneimine (PEI) in an organic solvent to prepare a PEI spinning solution with a mass concentration of 20-40%; diluting the PEI spinning solution with an organic solvent to a mass concentration of 5-15%, and then adding polyacrylonitrile (PAN) to prepare a PEI / PAN mixed spinning solution, wherein the mass ratio of PEI to PAN in the mixed spinning solution is 1:2 to 2:1; electrospinning the PEI / PAN mixed spinning solution to remove residual solvent, thereby obtaining a composite nanofiber membrane with a three-dimensional porous network structure.
[0008] Based on the above technical solution, the branched polyethyleneimine has an average molecular weight of 5000~30000 Da.
[0009] Based on the above technical solution, the average molecular weight of polyacrylonitrile is further 100,000~200,000 Da.
[0010] Based on the above technical solution, the organic solvent further includes N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0011] Based on the above technical solution, the specific process of dissolution is to stir at 50~70 ℃ for 2~6 h.
[0012] Based on the above technical solution, the process parameters for electrospinning are further as follows: voltage 15~25 kV, roller speed 400~600 rpm, feed speed 0.5~1.5 mL / h, and receiving distance 10~15 cm.
[0013] Secondly, the present invention provides a pH-responsive PEI / PAN composite nanofiber membrane prepared by the above-described preparation method.
[0014] Based on the above technical solution, the PEI / PAN composite nanofiber membrane further has a high specific surface area and a three-dimensional porous network structure. Through the electrostatic interaction between the amino groups in the PEI segments and DNA molecules, it can adsorb and store negatively charged DNA molecules. By adjusting the pH value of the system to change the protonation state of the PEI amino groups, the electrostatic force between PEI and DNA is weakened, thereby achieving the regulation of DNA molecule adsorption and release.
[0015] Thirdly, the present invention provides the application of the pH-responsive PEI / PAN composite nanofiber membrane in nucleic acid molecule storage.
[0016] Based on the above technical solution, the nucleic acid molecules further include DNA molecules and RNA molecules.
[0017] Based on the above technical solution, the application further includes pre-activation treatment, adsorption of nucleic acid molecules, and release of nucleic acid molecules.
[0018] Based on the above technical solution, the pre-activation treatment specifically involves immersing the PEI / PAN composite nanofiber membrane in a Britton-Robinson (BR) buffer solution with a pH of 7.0~8.0 for 5~30 min.
[0019] Based on the above technical solution, the adsorption process of the nucleic acid molecules is further as follows: the pre-activated PEI / PAN composite nanofiber membrane is placed in a BR buffer solution containing nucleic acid molecules and incubated for 20-60 min. Adsorption is achieved through the electrostatic interaction between the amino groups on the polyethyleneimine molecular chain and the phosphate backbone of the nucleic acid molecules.
[0020] Based on the above technical solution, the pH of the BR buffer solution containing nucleic acid molecules is further controlled between 7.0 and 8.0.
[0021] Based on the above technical solution, the specific process of releasing nucleic acid molecules is as follows: The PEI / PAN composite nanofiber membrane adsorbed with nucleic acid molecules is placed in a BR buffer solution with pH=9~11 and shaken for 1~3 hours to reduce the protonation degree of the amino groups of the polyethyleneimine molecular chain, thereby weakening the electrostatic interaction between polyethyleneimine and nucleic acid molecules and realizing the release of nucleic acid molecules.
[0022] Compared with the prior art, the present invention has the following significant advantages: (1) This invention utilizes the amino groups in PEI molecules to achieve efficient electrostatic adsorption of DNA molecules, thereby increasing the DNA storage capacity; (2) The present invention uses electrospinning technology to construct a three-dimensional porous nanofiber network, which increases the contact area between DNA and materials; (3) The PEI / PAN composite nanofiber membrane of the present invention has good pH response performance and can achieve controlled release of DNA by adjusting the environmental pH; (4) The raw materials used in this invention are readily available, and the electrospinning preparation process is mature and easy to operate. Attached Figure Description
[0023] To more clearly illustrate the embodiments of the present invention, the accompanying drawings involved in the embodiments will be briefly described below.
[0024] Figure 1 Scanning electron microscope (SEM) images of PAN nanofiber membrane (a) and PEI / PAN composite nanofiber membrane (b), scale bar: 5 µm; Figure 2 The stress-strain curve of the PEI / PAN composite nanofiber membrane is shown. Figure 3 The graph shows the change in zeta potential of the PEI / PAN composite nanofiber membrane in solutions with different pH values. Figure 4 Infrared spectrum of PEI / PAN composite nanofiber membrane; Figure 5 The contact angle test results are shown for pure PAN fiber membrane and PEI / PAN composite nanofiber membrane. Figure 6 The graph shows the capacity curve of DNA adsorption by the PEI / PAN composite nanofiber membrane. Figure 7 Agarose gel electrophoresis image of the supernatant from the DNA adsorption process of the PEI / PAN composite nanofiber membrane; Figure 8 Electrophoresis diagram to verify the stability of DNA in BR buffer solution system at pH=10; Figure 9 Agarose gel electrophoresis image showing the integrity of DNA released from the PEI / PAN composite nanofiber membrane. Detailed Implementation
[0025] The present invention will be described in detail below with reference to the embodiments. However, the implementation of the present invention is not limited thereto. Obviously, the embodiments described below are only some embodiments of the present invention. For those skilled in the art, other similar embodiments can be obtained without creative effort and all fall within the protection scope of the present invention.
[0026] Example 1 This embodiment provides a method for preparing a PEI / PAN composite nanofiber membrane, including the following steps: (1) First, take 3 g of branched polyethyleneimine solution (PEI, 25000 Da, Ron) and dissolve it in 10 mL of N,N-dimethylformamide (DMF). Stir magnetically at 60 °C for 4 h to make it fully mixed. After the solution is homogeneous, stop stirring to obtain a PEI spinning solution with a concentration of 30% (w / v).
[0027] (2) Take 1.80 mL of 30% (w / v) PEI spinning solution, add 3.20 mL of DMF to make 5 mL of mixed solution; stir magnetically for 30 min until the solution is completely homogeneous and does not separate into layers, then add 0.5 g of polyacrylonitrile (PAN, 150000 Da) to the above mixed solution, and continue to stir magnetically for 4 h at 60 °C until PAN is completely dissolved to form a homogeneous mixed spinning solution.
[0028] (3) Electrospinning was performed on the above mixed spinning solution. The process parameters were: voltage of 19 kV, roller speed of 500 rpm, feed flow rate of 1 mL / h, and receiving distance of 13 cm. The solution was allowed to stand and dry for 24 h to remove residual solvent and PEI / PAN composite nanofiber membrane was prepared.
[0029] Preparation of PAN nanofiber membranes: (1) Mix 0.5 g of polyacrylonitrile (PAN, 150000 Da) with 5 mL of N,N-dimethylformamide (DMF) to prepare a 5 mL mixed solution. Stir magnetically at 50 °C for 4 h to finally obtain a 10% (w / v) PAN spinning solution.
[0030] (2) Electrospinning was performed on the above spinning solution. The process parameters were: voltage of 15 kV, feed flow rate of 1 mL / h, and receiving distance of 13 cm. The solution was allowed to stand and dry for 24 h to prepare PAN nanofiber membrane.
[0031] Example 2 This embodiment characterizes the PEI / PAN composite nanofiber membrane prepared in Example 1. (1) Morphological characteristics: Figure 1 The images show scanning electron microscope (SEM) images of PAN nanofiber membranes and PEI / PAN composite nanofiber membranes. Pure PAN fibers have smooth surfaces and uniform diameter distribution. The modified PEI / PAN composite fibers, however, maintain a good three-dimensional porous network structure, with smooth fiber surfaces and no obvious adhesion or beading, demonstrating that the introduction of PEI did not impair the spinning and fiber-forming properties.
[0032] (2) Mechanical property testing: Figure 2 The figure shows the stress-strain curves of the PEI / PAN composite nanofiber membrane. As can be seen from the figure, the pure PAN fiber membrane exhibits obvious brittleness, with an elongation at break of only 28.1% and a tensile strength of 1.7 MPa. In contrast, the elongation at break of the PEI / PAN composite nanofiber membrane increases to 51.5%, and the tensile strength reaches 3.4 MPa. This indicates that the introduction of PEI significantly improves the flexibility of the fiber membrane, giving it excellent mechanical properties.
[0033] (3) Surface Zeta potential measurement: Figure 3 The figure shows the zeta potential variation curves of the PEI / PAN composite nanofiber membrane in solutions with different pH values. As can be seen from the figure, the zeta potential on the surface of the fiber membrane gradually decreases with the increase of the ambient pH value, showing a clear pH stimulus response dependence.
[0034] (4) Infrared spectral characterization: Figure 4 The image shows the infrared spectrum of the PEI / PAN composite nanofiber membrane. The pure PAN fiber membrane is visible at 2244 cm⁻¹. -1 A characteristic absorption peak was observed nearby, which is attributed to the stretching vibration of -C≡N in polyacrylonitrile. The PEI / PAN composite nanofiber membrane also showed a peak at 2244 cm⁻¹. -1 Characteristic absorption peaks were observed nearby, retaining the original -C≡N characteristic peak of PAN, and still present at 3267 cm⁻¹. -1 A very broad and strong absorption band appeared in the region, which is mainly attributed to the NH stretching vibration in the PEI molecular chain; at the same time, at 1645 cm⁻¹... -1 The region exhibited characteristic peaks of NH bending vibration. This result demonstrates that amino-rich PEI polymers have been successfully doped and stably complexed into the PAN fiber backbone, providing abundant active binding sites for subsequent efficient capture of DNA molecules via electrostatic interactions.
[0035] (5) Contact angle test: Figure 5 The figures show the contact angle test results for pure PAN fiber membranes and PEI / PAN composite nanofiber membranes. The pure PAN fiber membrane exhibits a contact angle of 44.35°, demonstrating certain hydrophilic wettability. In contrast, the PEI / PAN fiber membrane, due to the introduction of numerous highly polar and hydrophilic amino groups into the PEI molecular chain, shows a significantly enhanced hydrophilicity, with the contact angle decreasing to 32.98°. This substantial improvement in hydrophilicity facilitates the rapid and thorough penetration of DNA macromolecules into the deep three-dimensional porous network of the fiber membrane, thereby significantly improving the adsorption kinetics rate and overall fiber loading capacity.
[0036] Example 3 This embodiment examines the adsorption effect of the PEI / PAN fiber membrane prepared in Example 1 on DNA. (1) DNA preparation: The target DNA (1300bp) was diluted with Britton-Robinson (BR) buffer at pH 7.4 to prepare a 50 ng / μL DNA standard solution.
[0037] (2) Membrane pretreatment: Cut the PEI / PAN fiber membrane into 8 mm × 8 mm pieces, dry and weigh them, and then soak them in pH 7.4 BR buffer for 10 min for pretreatment to fully protonate the amino groups on the PEI chain. After the operation, use paper to fully absorb the residual moisture on the surface of the fiber membrane.
[0038] (3) DNA Adsorption: The experiment was divided into two groups. The control group received 100 μL of 50 ng / μL DNA standard solution; the experimental group received 100 μL of 50 ng / μL DNA standard solution slowly added to completely immerse the pretreated PEI / PAN fiber membrane. Both groups were incubated at room temperature for 30 min. At mins 5, 10, 15, 20, 25, and 30 during incubation, a small amount of supernatant was taken from each group. 3 μL of supernatant was used for subsequent electrophoresis analysis, and another 2 μL of supernatant was used to determine the remaining DNA concentration using a Nano Drop 2000 spectrophotometer. The adsorption capacity Q of the fiber membrane was calculated based on this. The formula for calculating the adsorption capacity is as follows:
[0039] C o (mg / μL) represents the initial DNA concentration in the solution, C e (mg / μL) is the DNA concentration in the solution at the predetermined time, V (μL) is the volume of the DNA solution, and M (g) is the weight of the membrane.
[0040] Figure 6 The figure shows the capacity curve of DNA adsorption by the PEI / PAN composite nanofiber membrane. As can be seen from the figure, at 30 min, the average adsorption capacity of the PEI / PAN composite nanofiber membrane is 2.64 mg / g, and the DNA adsorption rate is 68.60%.
[0041] The reserved supernatant samples were mixed with 6× DNA loading buffer and centrifuged, followed by agarose gel electrophoresis. The electrophoresis results are as follows: Figure 7 As shown, no obvious bands were observed in the supernatant of the experimental group, while a clear and bright band was observed in the control group at 1300 bp. This comparison indicates that the target DNA in the solution has been efficiently adsorbed by the PEI / PAN composite nanofiber membrane. At the same time, the clear and un-tailed bands in the control group confirm that the DNA backbone structure was not damaged in the pH=7.4 BR buffer system, maintaining good structural integrity and stability.
[0042] Example 4: Stability verification under alkaline conditions The DNA solution was mixed with pH=10 BR buffer to prepare a 50 ng / μL DNA mixed solution. Samples were taken at different time points (0 min, 30 min, 1 h, 1.5 h, 2 h, 2.5 h, and 3 h) at room temperature for agarose gel electrophoresis analysis. The results are as follows: Figure 8 As shown, after exposure to an alkaline environment for up to 3 hours, the electrophoretic bands at each time point remained clear and showed no obvious tailing or diffusion, proving that the BR buffer solution system at pH=10 would not cause DNA degradation and ensured the safety of the release process.
[0043] Example 5 This embodiment examines the release of DNA from the PEI / PAN fiber membrane. (1) The PEI / PAN composite nanofiber membrane with adsorbed DNA in Example 3 was immersed in 200 μL of BR buffer solution with pH=10 for elution. The total elution time was 2 h. During the elution process, the buffer solution was repeatedly aspirated and sprayed with a pipette to rinse the surface of the fiber membrane. The supernatant was aspirated every 30 min, and 3 μL of supernatant was collected for subsequent electrophoresis analysis.
[0044] (2) After mixing the above-mentioned retained release solution sample with 6×DNA loading buffer and centrifuging, perform agarose gel electrophoresis. The test results are as follows: Figure 9 As shown, a clear band was observed at 1300 bp, consistent with the location of the target DNA band. This result demonstrates that the composite nanofiber membrane successfully released DNA using an environmental pH-responsive method.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; modifications or equivalent substitutions may be made to the technical solutions described in the foregoing embodiments, and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a pH-responsive PEI / PAN composite nanofiber membrane, characterized in that, Branched polyethyleneimine (PEI) and polyacrylonitrile (PAN) were dissolved in an organic solvent to prepare a mixed spinning solution, which was then electrospun to prepare a composite nanofiber membrane with a three-dimensional porous network structure.
2. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: dissolving branched polyethyleneimine (PEI) in an organic solvent to prepare a PEI spinning solution with a mass concentration of 20-40%; diluting the PEI spinning solution with an organic solvent to a mass concentration of 5-15%, and then adding polyacrylonitrile (PAN) to prepare a PEI / PAN mixed spinning solution, wherein the mass ratio of PEI to PAN in the mixed spinning solution is 1:2 to 2:1; electrospinning the PEI / PAN mixed spinning solution to remove residual solvent, thereby obtaining a composite nanofiber membrane with a three-dimensional porous network structure.
3. The preparation method according to claim 2, characterized in that, The branched polyethyleneimine has an average molecular weight of 5,000 to 30,000 Da; the polyacrylonitrile has an average molecular weight of 100,000 to 200,000 Da; and the organic solvent includes N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
4. The preparation method according to claim 2, characterized in that, The electrospinning process parameters are as follows: voltage 15~25 kV, roller speed 400~600 rpm, feed speed 0.5~1.5 mL / h, and receiving distance 10~15 cm.
5. The pH-responsive PEI / PAN composite nanofiber membrane prepared by the preparation method according to any one of claims 1-4.
6. The application of the pH-responsive PEI / PAN composite nanofiber membrane according to claim 5 in nucleic acid molecule storage.
7. The application according to claim 6, characterized in that, The nucleic acid molecules include DNA molecules and RNA molecules; the applications include pre-activation treatment, adsorption of nucleic acid molecules, and release of nucleic acid molecules.
8. The application according to claim 7, characterized in that, The pre-activation treatment specifically involves immersing the PEI / PAN composite nanofiber membrane in a Britton-Robinson (BR) buffer solution with a pH of 7.0 to 8.0 for 5 to 30 minutes.
9. The application according to claim 7, characterized in that, The adsorption process of the nucleic acid molecules is as follows: the pre-activated PEI / PAN composite nanofiber membrane is placed in a BR buffer solution containing nucleic acid molecules and incubated for 20-60 min; the pH of the BR buffer solution containing nucleic acid molecules is controlled between 7.0 and 8.
0.
10. The application according to claim 7, characterized in that, The specific process of nucleic acid molecule release is as follows: The PEI / PAN composite nanofiber membrane adsorbed with nucleic acid molecules is placed in a BR buffer solution with pH=9~11 and shaken for 1~3 hours to achieve the release of nucleic acid molecules.
